ANALISIS PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KOMITMEN ORGANISASIONAL DAN IMBALAN FINANSIAL TERHADAP KEPUASAN KERJA KARYAWAN - Udayana, I Kadek; Riana, I Gede (E-Jurnal Manajemen, 2015)
This study aims to determine the effect of transformational leadership, organizational commitment, and financial rewards on employee job satisfaction. This research was conducted in Adma Umalas Villa with a number of samples were taken as many as 66 respondents, where respondents were all employees so that the sampling method used is the method of census. Multiple linear regression analysis was used to test hypotheses of the study. Based on the analysis we can conclude that the transformational leadership, organizational commitment and financial rewards positive and significant effect simultaneously on employee job satisfaction. Transformational leadership, organizational commitment and financial rewards positive and significant effect partially on employee job satisfaction.
Keywords: Job Satisfaction, Transformational Leadership Style, Organizational Commitment and Financial Rewards